Black Three in Personal Psychological Characteristics or Maciavelism, Psychopathy and Narsism - Rajabov Murodil Jumaboevich (Genius Publishing Group, 2022)
This article analyzes Machiavellianism, its history of origin, personality traits, and behavioral strategies. The Black Trinity is known for Machiavellianism, psychopathy, narcissism, and their brief descriptions.
Keywords: Machiavellianism; psychopathy and narcissism; Black Trinity; gazalting